Penggambaran Perkebunan Teh Kolonial Belanda Dalam "The Tea Lords" Karya Hella Haasse (1992) - Devi Rosliana Firdaus; Ririn Kurnia Trisnawati; Lynda Susana Widya A.F (Sapientia Humana: Jurnal Sosial Humaniora, 2024)
This research entitled "Portrayals of The Dutch Colonial Tea Plantation in Hella Haasse’s The Tea Lords (1992)," examines how the Dutch colonial tea plantation in Java is depicted in the novel. Set during Dutch colonization in the 19th century in the East Indies, the study uses the new historicism theoretical framework to analyze various portrayals of the plantation and their impact on East Indies society, culture, and economics. Employing qualitative methods, the researcher explores the historical context presented in the novel and history books to uncover the link between literary and non-literary texts. Findings reveal that the plantation significantly influenced East Indies society, culture, and economics, with the setting playing a central role in the narrative, providing readers with a deeper understanding of colonialism's impact. The research exposes economic disparities, highlighting exploitation and hierarchy in social and labor dynamics. Analysis of the Kerkhoven family sheds light on their challenges and moral dilemmas. Identity negotiation amid colonialism is explored, with the author's Dutch background influencing the novel's narration and conveying views on historical events. The study concludes that literature like The Tea Lords can challenge established historical narratives and is intertwined with broader cultural discourse.